Involving Problem-Based Learning as an Alternative for EFL Students’ Writing Improvement: A Method for Teaching Writing - Setlight, Kharisma C. M. S.; Betaubun, Martha; Kartika, Vicha (Journal of English Culture, Language, Literature and Education, 2023)
In fact, writing is one of the language skills that is emphasized in learning English in Curriculum 2013. As one of the language skills, writing skills need to be improved because it is a productive and expressive language skill that is needed to fulfill daily communication needs. Seeing the crucial role of writing, this present study intent to examine the problem based learning as an alternative model for EFL students’ writing improvement. Classroom action research with two cycles was implemented to study this phenomena. Moreover, this study involved 18 students of class XI SMA YPPK YOS SUDARSO Merauke, in collecting the data, this study used observation sheet for both teacher and students’ activities, meanwhile to see students’ writing improvement, explanation text writing was applied in both cycles. As the result, Problem based learning could improve students’ writing, it could be seen in each cycles’ scores, where cycle I writing was 63.33% and improved in cycle II 81%. In cycle I, most of students did not pass the minimum completeness which was 75, meanwhile in cycle II most of students passed. The improvement based on the observation results in both cycles are also being the success category in this study, in cycle I both teacher and students obtained 67.85% (good category) and 57.14% (enough category), improved in cycle II which was 87.5 (excellent category) and 83.92% (excellent category).